Studenterfaringer med veiledning og læring knyttet til deltagelse i et kvalitetsforbedringsprosjekt på sykehus med kunnskapsbasert praksis som arbeidsform, -en beskrivende og utforskende studie - Røkholt, Gro; Davidsen, Liv-Signe; Johnsen, Heidi Ness; Dihle, Alfhild (Nordisk tidsskrift for helseforskning, 2020)
Student experiences with supervision and learning through participation in a quality improvement evidence-baced practice project in a hospital, -a descriptive and explorative study A significant part of health care students’ education is provided through clinical placement supervised by practitioners with required education and experience. This study has been conducted to increase knowledge of students’ experiences with supervision and learning related to participation in a quality improvement project in a hospital using evidence-based practice tools. A descriptive and exploratory design with focus group interviews. Data was analysed using qualitative content analysis. Three main themes emerged: changed student role, understanding the importance of keeping professional knowledge updated and need for the facilitation of the clinical placement period. The study showed that supervision helped students become equals of their supervisors and part of the community of practice. The project contributed to students`’ coping skills. Integrating evidence-based practice into practice taught students a method of professional knowledge updating and quality improvement.